Biological, Psychological, and Social Predictors of Longevity Among Utah Centenarians. (October 2018) - Yorgason, Jeremy B.; Draper, Thomas W.; Bronson, Haley; Nielson, Makayla; Babcock, Kate; Jones, Karolina; Hill, Melanie S.; Howard, Myranda
Studies of longevity among centenarians examine biological, psychological, and social factors, yet few consider these components concurrently. This study explores such factors individually and collectively, as they are related to days lived past the age of 100 years. Data from 268 family members of centenarians identified in the State of Utah between 2008 and 2015 were used in negative binomial models predicting number of days lived among the centenarians. Findings suggested that sleep latency (biological), life satisfaction (psychological), and attachment closeness (social) were predictive factors of more days lived within individual models. When considered together, sleep latency and life satisfaction remained significant predictors of days lived. Although biological factors are commonly considered in relation to longevity, this study further indicates that psychological and social factors may play important roles in life expectancy. Further examination is needed to explore how these factors link additionally to active life expectancy.